The Self-Efficacy and Disaster Preparedness of Coastal Nurse in Jember: Self-Efficacy and Disaster Preparedness of Coastal Nurse in Jember - Rismawan Adi Yunanto; Rondhianto; Baskoro Setioputro; Ruris Haristiani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2023)
Coastal areas in Jember Regency have a high risk of getting a big impact if an earthquake and tsunami. These potential disasters force all elements to be prepared to face disasters that can arise anytime, including nurses in the Coastal Public Health Center of Jember. Self-efficacy is thought to have a relationship in improving nurse preparedness in dealing with disaster situations. The aim of this research is to analyze and describe the relationship between the self-efficacy of coastal nurses and the level of preparedness of nurses in dealing with earthquakes and tsunamis in Jember. This study was a correlational research study with a cross-sectional approach. The population of this study was 161 nurses. The sampling method used was convenience sampling, with the total number of nurses participating in this study was 144. We used two main questionnaires to collect the data: the General Self-Efficacy (GSE) and the Disaster Preparedness Evaluation Tool (DPET). We analyzed the data using Pearson Product moment with a significant level (α) =0.05. We found a significant correlation between the disaster preparedness and self-efficacy of the coastal nurse in Jember with a p-value of 0,008 (< 0.05). The degree of relationship was 0.619, which is considered significant and positive. There is a relationship between self-efficacy and nurse preparedness in dealing with disasters. The association is in a positive direction, meaning that the higher the level of self-efficacy, the higher the nurse's disaster preparedness. Keyword: Disaster Preparedness, Self-efficacy, Coastal nurse, Coastal Areas of Jember